KOLABORASI ANTARA KAFE BERTEMA UNITY IN SIMILARITY DAN KANTOR TRAVEL AGENT DENGAN TEMA FIRST IMPRESSION - Sisca Natalia Suhartono; Freddy Handoko Istanto; Rani Prihatmanti (Universitas Ciputra Surabaya, 2016)
Industries nowadays such as foods and beverages are growing rapidly. The growth is triggeredby public’s necessity in needing an informal places for socializing. This happens because there is a shiftin a lifestyle especially in foods and beverages’ market demands, which was originally just to come anddine becoming to dine and socialize. Today the industry players of these industries are insisted by publicto present a different concept and atmosphere to answer the customers’ needs and one of them is throughinterior design. With a good display and a supportive interior design, it will attract public and will give aconvenience for customers. Based on existing opportunities, CONCEPTICO Interior Design Consultantoffers an interior design service to answer public’s needs especially on a commercial projects such ascafes and restaurants. According to the CONCEPTICO Interior Design Consultant’s service, therefore theNoodle Bar and the Agra Travel Agency, which located in Mojokerto, become one of the exact case studies.This business is from the previous business which will be developed, however the interior design has notdesigned yet. Therefore to solve the problem, CONCEPTICO Interior Design Consultant gives solution byproviding a good services by paying attention to spatial, layouts, aesthetics, circulations, and concepts orstyles which will be created.